DESAIN DAN IMPLEMENTASI RAISED BED PADA LAHAN KWT SEBAGAI TAHAP AWAL PENGEMBANGAN SISTEM INTEGRATED FARMING - Septi Wulandari; Ani Apriani; Paramitha Tedja Trisnaning (Jurnal Abdi Insani, 2026)
This community service program was implemented with the Kelompok Wanita Tani (KWT) Pradan Makmur under the PKK organization, located in Dusun Pradan, Geneng Village, Prambanan District, Klaten Regency, Central Java, Indonesia. The main problems faced by the partner included inefficient land arrangement, low soil fertility and susceptibility to waterlogging, limited understanding of cultivation technology, and the absence of an integrated and sustainable farming concept. These conditions resulted in low land productivity and limited contribution of agricultural activities to the food security and economic independence of KWT members. As a solution, the program focused on the design and implementation of a raised bed system as the initial stage in developing an integrated farming system. The implementation method was participatory, consisting of socialization, comparative study visits, training, technology application, mentoring, and evaluation. Lecturers, students, and KWT members were actively involved in land layout planning, construction of raised beds using recycled materials, establishment of living fences from cassava stems, and management of planting media and simple irrigation systems. The results demonstrated significant improvements in land organization and soil quality, farming skills, and participants’ understanding of raised bed systems and integrated farming concepts. Based on pre-test and post-test results, participants’ understanding increased from low and moderate categories to 100% in the high category. Statistical analysis using the Wilcoxon Signed Ranks Test indicated a significant difference in participants’ understanding of integrated farming and crop management before and after the program. The outputs of this program included raised bed facilities, planting media based on recycled materials, living fences, activity documentation, and a follow-up plan for developing the integrated farming system. The implementation was also documented in a video uploaded to YouTube and presented in a poster. Overall, the program had a positive impact on enhancing the partner’s capacity and has the potential to serve as a community-based sustainable agriculture pilot model.